Decomposition of needle/leaf litter from Scots pine, black cherry, common oak and European beech at a conurbation forest site - Lorenz, Klaus; Preston, Caroline M.; Krumrei, Susan; Feger, Karl-Heinz (European journal of forest research, 2004)
Litter decomposition was studied for 2 years in a mixed forest serving as a water protection area (Rhine-Neckar conurbation, SW Germany). Two experiments differing in initial dry weight equivalent in litterbags were set up: one to compare decomposition of European beech leaves (Fagus sylvatica) with common oak leaves (Quercus robur), and the other comparing decomposition of Scots pine needles (Pinus sylvestris) with black cherry leaves (Prunus serotina Ehrh.), respectively. Mass losses were greater for oak litter than for beech (75.0 versus 34.6%), and for cherry litter than for pine (94.6 versus 68.3%). In both experiments, a strong initial loss of soluble compounds occurred. The changes in litter N and P concentrations and the decrease in C-to-N ratio coincided with changes in residual mass. However, neither tannin and phenolic concentrations nor NMR could explain the pronounced variation in mass loss after 2 years. Differences in litter palatability and toughness, nutrient contents and other organic compounds may be responsible for the considerable differences in residual mass between litter types. The fast decay of black cherry leaves appears to play a major role in the present humus dynamics at the studied site. Since black cherry has a high N demand, which is mainly met by root uptake from the forest floor, this species is crucial for internal N cycling at this conurbation forest site. These effects together may significantly contribute to prevent nitrate leaching from the forest ecosystem which is subject to a continuous N deposition on an elevated level.[PUBLICATION ABSTRACT]